The influence of frame pitch and stiffness on the stress distribution in pressurised cylinders - Houghton, D. S. (College of Aeronautics, 1958)
An analysis is made of the stresses occurring in stringer reinforced cylinders due to the restraining action of the frames. Graphs are presented showing the effect of variation in frame pitch and stiffness, on the bending moment and shear force in the skins, and the hoop stress in the skins between frames. The results are used to show how the optimum structural geometry can be chosen for any given stress ratios.